A validated CFD model for prediction of selective non-catalytic reduction of nitric oxide by cyanuric acid. (2016) - Burström, Per E.C.; Antos, Dorota; Lundström, T. Staffan; Marjavaara, B. Daniel
A CFD model for selective non-catalytic reduction of nitric oxide by cyanuric acid (rapid reduction of nitrogen oxides, RAPRENOx process) is compared against reactor experiments. The numerical simulations were carried out solving the flow field. A model for the RAPRENOx chemistry was then included in the model enabling a study of the chemistry in the reactor. The simulations showed that the proposed chemistry model is valid under certain conditions. There is an especially good agreement for high O2 concentrations while the model failed in reproducing the experimental data for 0% H2 O.